Analisis Kesiapan Pembelajaran Bahasa Jepang Secara Daring di Masa Pandemi Covid-19 pada SMA Negeri 1 Kubutambahan - Komang Tegar Abdi Wangsa; Kadek Eva Krishna Adnyani; Yeni Rahman (Jurnal Penelitian Mahasiswa Indonesia, 2023)
The purpose of this research is to analyze the preparedness for learning Japanese in a courageous manner during the Covid-19 pandemic at SMA Negeri 1 Kubudinding in the 2020/2021 academic year. The subjects in this study were 177 students of SMA Negeri 1 Kubudinding who received Japanese as a subject. The research method used was structured interviews and open and closed questionnaires. In this study using the theory of Chapnick (2000) and Kebritchi, et al (2017) regarding learning readiness for students, teachers and materials. The research model used for data analysis is the E-Learning readiness research model by Aydin and Tasci (2005). The results showed that student readiness had a total ELR score of 3.34, teacher readiness had an ELR score of 3.36 and material readiness had an ELR score of 3.34. The third factor is included in the same category, namely not ready and still needs effort. Thus the level of readiness for learning Japanese boldly at SMA Negeri 1 Kubu added is declared not ready and still needs effort.